PERSPEKTIF SISWA SMP NEGERI TERHADAP NOS (NATURE OF SCIENCE) DI KABUPATEN PATI - Alis Rahmawati; Eko Retno Mulyaningrum (Universitas PGRI Semarang, 2016)
ABSTRACTThis study aims to obtain the information about the students perspectives of SMP Negeri against NOS (Nature of Science) in Pati regency. The subject of the study are 339 of 8th grade students from SMP Negeri 16 in Pati District. The instrument of data collection is a test description which consist of analysis based on seven aspects of NOS with 7 questions that have developed by researcher. The result shows the understanding of NOS in 8th grade junior high school students in Pati District classified as “poor” with score 39.12% in general. The implication of this research is the new knowledge that NOS aspect should be taught in schools explicitly so students can understand NOS well. Keywords: Nature of Science (NOS), perspective, students SMP Negeri in Pati regency.ABSTRAKPenelitian ini bertujuan untuk memperoleh informasi mengenai perspektif siswa SMP Negeri terhadap NOS (Nature of Science) di Kabupaten Pati. Subjek penelitian yang digunakan adalah 339 siswa kelas VIII dari 16 SMP Negeri di Kabupaten Pati. Instrumen pengumpulan data adalah tes uraian berupa analisis berdasarkan 7 aspek NOS berjumlah 7 soal yang telah dikembangkan peneliti. Hasil penelitian menunjukkan bahwa secara umum perspektif NOS pada siswa SMP di Kabupaten Pati tergolong kurang yaitu hanya 39,12%. Implikasi dari penelitian ini adalah pengetahuan tentang aspek NOS seharusnya diajarkan di sekolah-sekolah secara eksplisit sehingga siswa dapat memahami NOS dengan baik.Kata kunci: Nature of Science (NOS), perspektif, siswa SMP Negeri di Kabupaten Pati.